High-precision topographical methodology for determining height differences when crossing impassable areas. (March 2018) - Bitelli, Gabriele; Roncari, Gianfranco; Tini, Maria Alessandra; Vittuari, Luca
Highlights: High-precision topographic total stations are used to cross impassable areas. Trigonometric levelling is proposed as an alternative to geometric levelling. The procedure is based on a reciprocal and simultaneous levelling scheme. The right geometrical and timing schedule, and the calibration of ATR are required. Abstract: With the arrival on the market of high-precision topographic total stations, professionals today, using appropriate methodologies, can determine altimetric connections to an accuracy that is almost comparable to those obtainable using high-precision geometric levelling. This aspect is of particular interest when it is not possible to proceed with classical geometric levelling operations due to logistical or other reasons: for instance, where levelling lines need to cross impassable areas such as streams, soft soils or canyons. Currently, height differences between two points separated by an impassable area are mainly measured using optical-mechanical levels by procedures that present a number of difficulties. This work presents the results achieved through several trials conducted on the use of high precision trigonometric levelling for measurement of height difference between benchmarks at opposite sides of streams. In particular, it describes the project where simultaneous and reciprocal measures were taken using two high-precision robotic total stations.